The Trials of Edward Vaughan - Bowen, Lloyd (University of Wales Press, 2025)
This book tells a remarkable story. Edward Vaughan was the fifth son of a landed gentleman, and could not have expected much beyond a career in law. However, by fair means and foul (mostly foul), he managed to gain possession of one of the largest estates in seventeenth-century Wales. His tenure was not to be a quiet one, however, as the Protestant Vaughan endured a bruising legal contest with a powerful Catholic magnate over these lands. Vaughan’s case was then swept up in the politics of the civil wars. A moderate parliamentarian, during the 1640s and 1650s Vaughan fought new battles with local radicals to secure his patrimony. The trials of Edward Vaughan reveal much about the confrontational and sometimes bloody nature of law, politics and faction in early modern England and Wales. It is a rich and surprising story, and one which has yet to be told.